ECOLOGICAL AND ECONOMIC POTENTIAL OF WATER BASINS IN CONDITIONS OF CLIMATE CHANGE AND IRRATIONAL NATURE MANAGEMENT - Клименко, Николай; Гриб, Иосиф; Войтишина, Диана (SWorldJournal, 2021)
Just considering the basins of the rivers as the primary cell of the economic research, we have assessed the situation in three components: the biological productivity (B), water quality of environmental index (Ie) and the capacity of water channels (Qр